Chief Police Officers’ Stories of Legitimacy: Power, Protection, Consent and Control - Shannon, Ian (Palgrave's Critical Policing Studies, 2022)
1 Introduction -- 2 Legitimacy: A Contested Concept -- 3 Chief Police Officers’ Backgrounds and Motivations -- 4 Protecting People, Particularly the Most Vulnerable -- 5 Policing by Consent -- 6 Law and Governance -- 7 Conclusion.